XXIV-th Open Seminar On Acoustics - BUDZYŃSKI, Gustaw (Archives of Acoustics, 1978)
The XXIV-th Seminar on Acoustics was held at Wladyslawowo at Gdansk, September 19-24. The seminar was sponsored by the Gdansk Section of the Polish Acoustical Society in cooperation with the Committee on Acoustics of the Polish Academy of Sciences, the Ins¬titute of Telecommunication of Gdansk Technical University and the Institute of Physics of Gdansk University. 360 persons, participated in the seminar including from abroad. There were acousticians from Czechoslovakia, Denmark, France, GDR, Japan, Netherlands, Spain, Switzerland, USSR. Out of the 322 home participants nearly half were members of the Polish Acous¬tical Society.